Mineral resources of Costa Rica - _, Anónimo (Universidad de Costa Rica, 2011)
The history of Costa Rica [Fig. 1] mining But enough of the past! This progressive operations reaches back into colonial times. Some country with its varied national wealth, which the of the largest gold mines have been worked in a Spaniards named “Costa Rica”, with good reason primitive way with success for several centuries, now arouses a lively interest in other countries. and the mineral treasures brought up to the light Distinguishing itself for a long time past from the of day by the old Spanish gold seekers are said other countries of Central America to its advan- to have been almost fabulous. One of the richest tage with its stable and responsible Government, gold mines called Tisingall, had to be abandoned this still scantily-populated republic offers oppor- because of the hostility of the native Indians ; tunities for investment of foreign capital equalled the mine itself was then completely destroyed by by few countries. It is abundant and diversified them, and the locality closes up by changing the mineral wealth, which is coming more and more course of the neighbouring streams. After quelling to the front, is already attracting the attention of the uprising it was impossible for the Spaniards to large capitalists today.